2019
DOI: 10.1016/j.jpeds.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prophylaxis for Early Adrenal Insufficiency Using Low-Dose Hydrocortisone in Very Preterm Infants: An Individual Patient Data Meta-Analysis

Abstract: Objective To assess the effect of prophylaxis for early adrenal insufficiency using low-dose hydrocortisone on survival without bronchopulmonary dysplasia (BPD) in very preterm infants using an individual patient data meta-analysis. Study design All existing randomized controlled trials testing the efficacy of the prophylaxis of early adrenal insufficiency using low-dose hydrocortisone on survival without BPD were considered for inclusion when data were available. The primary outcome was the binary variable su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 36 publications
(62 reference statements)
3
57
2
2
Order By: Relevance
“…In addition, infants presenting with symptoms and signs of hypotension are sometimes treated with a stress dose of steroids. Thus, an individual patient data meta-analysis, including five eligible studies in extremely preterm infants, evaluating the efficacy of using early low-dose hydrocortisone as prophylaxis of adrenal insufficiency demonstrated that the therapy is beneficial for survival without BPD [100]. The most updated results for the use of hydrocortisone came from the PREMILOC trial [101].…”
Section: Hydrocortisonementioning
confidence: 99%
“…In addition, infants presenting with symptoms and signs of hypotension are sometimes treated with a stress dose of steroids. Thus, an individual patient data meta-analysis, including five eligible studies in extremely preterm infants, evaluating the efficacy of using early low-dose hydrocortisone as prophylaxis of adrenal insufficiency demonstrated that the therapy is beneficial for survival without BPD [100]. The most updated results for the use of hydrocortisone came from the PREMILOC trial [101].…”
Section: Hydrocortisonementioning
confidence: 99%
“…Dexamethasone is not recommended as routine treatment and should be considered only for infants who are mechanically ventilated after 2 weeks of life [6][7][8]. Recommendations about PNC may change in the future as prophylactic low-dose hydrocortisone has recently been shown to improve survival without BPD [9] with no statistically significant difference in neurodevelopment at 2 years of age [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Adding to this complexity is the differential impact of these interventions on neonatal outcomes. For example, a recent individual patient data meta‐analysis has shown that use of prophylactic indomethacin to prevent IVH will preclude the use of prophylactic hydrocortisone to improve survival without CLD as their concomitant use increases the risk of spontaneous intestinal perforation (OR 2.50; 95% CI, 1.33 to 4.69) . This study highlights how the use of some interventions could improve some clinical outcomes while potentially worsening others.…”
Section: Why Are Family Values and Preferences Important In Neonatal mentioning
confidence: 99%